Identification of novel vaccine candidates against carbapenem resistant Klebsiella pneumoniae: A systematic reverse proteomic approach. (December 2020) - Mehmood, Asim; Naseer, Samar; Ali, Amjad; Fatimah, Hina; Rehman, Shazia; Kiani, Aysha Karim
Graphical abstract: Highlights: To predict novel antigenic peptides for vaccine development against Klepsiellae pneumonia by utilizing reverse vaccinology approach. The whole proteome of K. pneumonia e was analyzed using bioinformatics tools. Eight antigenic proteins were predicted as novel targets for vaccine design against multidrug resistant K. pneumoniae . Abstract: Klebsiella pneumoniae is declared as antibiotic resistant by WHO, with the critical urgency of developing novel antimicrobial therapeutics as drug resistance is the second most dangerous threat after terrorism. Besides many attempts still, there is no effective vaccine available against K. pneumoniae . By utilizing all the available proteomic data we prioritized the novel proteins ideal for vaccine development using bioinformatics tools and techniques. Among the huge data, eight proteins passed all the barriers and were considered ideal candidates for vaccine development. These include: copper silver efflux system outer membrane protein (CusC), outer membrane porin protein (OmpN), Fe ++ enterobactin transporter substrate binding protein (fepB), zinc transporter substrate binding protein (ZnuA), ribonuclease HI, tellurite resistant methyltransferase (the B), and two uncharacterized hypothetical proteins (WP_002918223 and WP_002892366). These proteins were also subjected to epitope analysis and were found best for developing subunit vaccine against K. pneumoniae. The study shows that the potential vaccine targets are sufficiently efficient being virulent, of outer membranous origin and can be proposed for the DNA third-generation vaccines development that would help to cope up infections caused by multidrug-resistant K. pneumoniae .